Socialization, cultivation, and utilization of empty land for family medicinal plants - Dita Natasya; Muhammad Gilang Ramadhan Tunggeng; Pahdila Rezki Annisa; Nur Isra Nopianti; Maghfira Meyghafary Anhariza Dawa; Nuurhidayat Jafar; Asdar Gani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
The prevalence of illness complaints among the Indonesian population is 228.15 percent, with 65.01 percent opting for self-treatment using synthetic drugs, while 38.30 percent prefer traditional medicine. The use of traditional medicines in communities, including in Katimbang Village, remains significantly lower compared to synthetic alternatives. A comprehensive strategy is needed to enhance public knowledge and understanding of how to obtain and utilize traditional medicine from medicinal plants found around the home. This socialization and cultivation activity was conducted at Integrated Service Post (Posyandu) RW 04, Katimbang Village, involving 21 community members. The event included a socialization session on family medicinal plants, pre- and post-tests, Q&A discussions, and the planting of 50 medicinal plant seeds, with participation from students and local residents. Statistical tests revealed the success of this intervention in improving participants' understanding of medicinal plants, with an average pre-test score of 8.4762 increasing to 8.6190 in the post-test. More than 50 percent of participants scored ≥80 in the post-test. The success of this outreach and planting activity provides a strong foundation for further increasing public awareness of the use of medicinal plants as complementary treatments for various illnesses.